Pengaruh Return On Equity (ROE) dan Earning Per Share (EPS) terhadap Harga Saham pada Perusahaan PT Bank Rakyat Indonesia Persero Tbk Periode 2015 – 2024 - Agus Suhartono; Vidya Amalia Rismanty; Tri Wartono (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The background of this research is based on the importance of financial performance indicators in influencing investor decisions and stock market movements. ROE and EPS are commonly used to assess a company’s profitability and its attractiveness in the capital market, yet their effects on stock prices may vary depending on market conditions and investor perceptions. This study examines the effect of Return on Equity (ROE) and Earnings per Share (EPS) on the stock price of PT. Bank Rakyat Indonesia Tbk during the period 2015–2024. This study employs a quantitative associative approach using secondary data obtained from official financial reports and the company’s website. The data were analyzed using descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), and hypothesis testing (t-test and F-test) with the assistance of SPSS version 26. The results indicate that ROE has a negative and insignificant effect on stock prices, while EPS has a positive and significant effect. Simultaneously, ROE and EPS significantly influence stock prices, with an R² value of 0.959, meaning that 95.9% of stock price variation is explained by these variables.